2016
DOI: 10.1177/2150135116651113
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Valve Replacement With Small Intestine Submucosa-Extracellular Matrix in a Porcine Model

Abstract: The SIS-ECM valved conduit implanted into a piglet demonstrated cellular infiltration with vascular remodeling and an increase in diameter. Conduit stenosis was a result of slower rates of size increase than native tissue. Suboptimal leaflet performance requires design modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 31 publications
0
27
1
Order By: Relevance
“…Initial research showed good valve function and progressive endothelialization and constructive remodeling in the short-term in porcine, ovine, and human atrioventricular and pulmonary valves. 5,19,20 Miller and colleagues 6 showed advanced remodeling in the pig pulmonary position with myofibroblast infiltration, endothelialization, and conduit growth. Despite this remodeling, all animals eventually developed significant valve dysfunction within 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial research showed good valve function and progressive endothelialization and constructive remodeling in the short-term in porcine, ovine, and human atrioventricular and pulmonary valves. 5,19,20 Miller and colleagues 6 showed advanced remodeling in the pig pulmonary position with myofibroblast infiltration, endothelialization, and conduit growth. Despite this remodeling, all animals eventually developed significant valve dysfunction within 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this remodeling, all animals eventually developed significant valve dysfunction within 6 months. 6 Incomplete resorption and disorganized degradation of pSIS-ECM accompanied by chronic inflammation, fibrosis, and calcification led to progressive mechanical and remodeling failure at 4 to 6 months in small preclinical studies in pig aortic valve. 21,22 In line with these findings, the largest recent clinical studies on valve repair using CorMatrix have shown functional failure at short-and midterm follow-up with high reoperation rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 SIS grat has been successfully used in human medicine for urinary, 32 orthopaedic, 33 and abdominal wall surgery 34 and in veterinary patients for vascular grating, 35 esophageal reconstruction, 36 tendon reconstruction 37 38 and cardiac valve replacement. 39 In veterinary ophthalmology, the use of SIS is reported for corneal reconstruction ater limbal melanocytoma excision in a dog, 19 in diferent corneal disease in cats, 20 combined with conjunctival lap in cat, dog and horse, 21 in deep melting ulcers combined with nictitating membrane lap, 22 and with the use of one or more discs stacked depending on the depth of the lesion. 23 SIS scafolds have an acellular collagen composition, they are not immunogenic and act as an inductive substrate which induces tissue healing by stimulating migration, diferentiation and proliferation of sitespeciic cells, while conferring mechanical resistance to the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…After experimental ( 6 8 ) and clinical ( 9 11 ) studies, the decellularized porcine small intestine sub-mucosa (DPSIS) patch has been introduced with the commercial name of CorMatrix® (CorMatrix Cardiovascular, Roswell, GA) for the surgical treatment of congenital heart defects, with implantations performed for closure of septal defects, valve repair, and as vascular patch in both the systemic and pulmonary circulations ( 12 16 ).…”
Section: Introductionmentioning
confidence: 99%